#TITLE_ALTERNATIVE# - NOVARRO BATUBARA (NIM 25005031), BEN
This thesis is aim to study the replaceable shear link with end plate flush typed. The numerical analysis is carried out using NASTRAN & PATRAN 2005 software to study the performance of replaceable link due to variation of parameters: bolt diameter, end plate thickness, end plate dimension, link length and extended flanges. The analytical model is used to study ductility, rigidity, load capacities and energy dissipation with cyclic and monotonic loading. The results show that the parameters of bolt diameter, end plate thickness, end plate dimension and extended flanges improve the energy dissipation and structural rigidity. The extended flanges have been able to contribute the stress distribution equally to all elements of structure that cause the plasticity process which relate to the increase of the ductility value of structure.